Artificial intelligence in cloud-based mobile radar computing - Коsovets, M.; Tovstenko, L. (Інститут програмних систем НАН України, 2023)
The introduction of Artificial Intelligence into mobile radar computing based on cloud resources has made it possible to combine radar resources at the stage of receiving, processing and presenting information. The radar system has become integral and flexible. The convergence of mobile applications in portable devices with cloud computing is a revolution in the organization of distributed computing. Attention is paid to the architecture of the client part as a neurocomputer distributed in space with deep learning capabilities. Providing analysis of radar data in Real Time for a mobile platform is very important and its implementation with packet data transmission at different stages accelerate the analysis process.Problems in programming 2023; 2: 49-58